PENGARUH CURRENT RATIO (CR) DAN NET PROFIT MARGIN (NPM) TERHADAP HARGA SAHAM PADA PT HANJAYA MANDALA SAMPOERNA TBK PERIODE 2013-2022 - Submission JORAPI; Lutfia Surya Wardani; Yulian Bayu Ganar (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of Current Ratio (CR) and Net Profit Margin (NPM) both partially and simultaneously on share prices at PT Hanjaya Mandala Sampoerna Tbk for the 2013-2022 period. The method used in this research is a descriptive research method with a quantitative approach. The population in this research is all financial reports of PT Hanjaya Mandala Sampoerna Tbk for the 2013-2022 period. The sample used in this research is the balance sheet and profit and loss report of PT Hanjaya Mandala Sampoerna Tbk for the period 2013-2022. The analysis techniques used are Descriptive Analysis Test, Classic Assumption Test, Multiple Regression Analysis, Hypothesis Test (t Test, F Test) and Determination Coefficient Test (R2). Based on the research results, it shows that the Current Ratio partially has a significant effect on the share price at PT Hanjaya Mandala Sampoerna Tbk for the 2013-2022 period. Net Profit Margin partially has a significant effect on the share price of PT Hanjaya Mandala Sampoerna Tbk for the 2013-2022 period. Current Ratio and Net Profit Margin simultaneously have a significant effect on the share price of PT Hanjaya Mandala Sampoerna Tbk for the 2013-2022 period.